(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
The most important element of the ancient houses was the inner courtyard and the rooms were usually arranged around it. In the closing years of the fifth century > BC certain innovations were made in the houses: the courtyard acquired a peristyle. These peristyles had formed the central courtyard of Hellenistic houses like those preserved at Delos and Priena. The peristyle derives from Greek public architecture. When transplanted to roman houses they become articulated gardens, located whenever possible on the atrium axis in order to extend to the maximum the long view from the central door. The only limit on the luxury of the peristyle was the owneres purse. These spaces housed new rituals of pleasure and self presentation made possible not only by wealth but also by the architects who emigrated from the devastated east. The roman houses in the Republic of Macedonia are characterized by a central peristyle with burgeoning vegetation and richly decorated fountains, which pleased the ear and offered refreshment. The great achievement of the peristyle was that it brought the garden right inside the house. Need for elegance is explicitly linked to position in the hierarchical rank. The disappearance of the Roman peristyle house, says S. Ellis, marks the end of the ancient world and its way of life.